2020
DOI: 10.1111/jace.17492
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of the nanolayered Fe2AlB2 in nitrogen and argon atmospheres

Abstract: The MAB phases are atomically laminated ternary or quaternary transition metal (M) borides whose crystal structures are comprised of stacked M-B (M = transition metal; B = boron) layers interlayered with one or two layers of an A element (Al or Zn). 1,2 The MAB phase Fe 2 AlB 2 has garnered considerable research attention for its electrocatalytic water-splitting ability, 3 favorable high-temperature mechanical properties, 4 and for being a promising magnetocaloric material for active magnetic regenerative refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In general, materials’ thermal stabilities decrease with increasing TECs, which means a lower decomposition temperature 55 . Through the above calculation, it can be found that the ranking of TECs of the three compounds is Mn 2 AlB 2 > Fe 2 AlB 2 > MoAlB, which is consistent with the ranking of MoAlB > Fe 2 AlB 2 > Mn 2 AlB 2 in terms of thermal stabilities 34,35,56 …”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In general, materials’ thermal stabilities decrease with increasing TECs, which means a lower decomposition temperature 55 . Through the above calculation, it can be found that the ranking of TECs of the three compounds is Mn 2 AlB 2 > Fe 2 AlB 2 > MoAlB, which is consistent with the ranking of MoAlB > Fe 2 AlB 2 > Mn 2 AlB 2 in terms of thermal stabilities 34,35,56 …”
Section: Resultssupporting
confidence: 66%
“…55 Through the above calculation, it can be found that the ranking of TECs of the three compounds is Mn 2 AlB 2 > Fe 2 AlB 2 > MoAlB, which is consistent with the ranking of MoAlB > Fe 2 AlB 2 > Mn 2 AlB 2 in terms of thermal stabilities. 34,35,56…”
Section: Compoundsmentioning
confidence: 99%
“…In previous studies, the intrinsic structural [3,4], mechanical [5,6], electrical [7,8], magnetic [9,10], thermal [11][12][13], optical [14,15], oxidation resistant [16], crack healing [17], radiation tolerant [18,19], friction and wear properties [20][21][22] and machinability [4] of these materials as well as the underlying mechanisms have attracted a lot of attention and investigated both through first-principles calculations and as experimentally synthesized powder [23], ceramic pellet [24] and coating [25]. In recent years, the influence of different synthetic method [26][27][28][29], coating deposition condition [30,31] and application environment [32][33][34][35] on these properties have also been taken into consideration. Doping and solid-solution have been introduced to further improve the mechanical, electrical, thermal and oxidation resistant properties of these two materials [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…According to Kota et al [10], the experimentally prepared MAB phases can be represented by the general formula of (MB) 2z A x (MB 2 ) y (z = 1, 2; x = 1, 2; y = 0, 1, 2), including MAlB, M 2 AlB 2 , M 3 AlB 4 , M 4 AlB 6 , and M 4 AlB 4 with abbreviation of 222, 212, 314, 416, and 414 phases, respectively. In these compounds, MB sublattices are separated by two layers of Al in the MAB phases, such as MoAlB [11], or a single layer of Al in phases such as Fe 2 AlB 2 [12], Cr 2 AlB 2 [13], Cr 3 AlB 4 , Cr 4 AlB 6 , Cr 4 AlB 4 [14][15][16], and Mn 2 AlB 2 [17]. Other than the initial MAB phases, new layered borides including Nb 2 SB [18], Y 5 Si 2 B 5 [19], V 2 AlB [20], Zr 3 CdB 4 [21], V 5 Si 3 B [22], and Hf 2 PdB [23] have also been reported, which riches the family of MAB phases.…”
Section: Introduction mentioning
confidence: 99%